2020
DOI: 10.1177/0951484820952307
|View full text |Cite
|
Sign up to set email alerts
|

Organizational commitment among physicians: A systematic literature review

Abstract: Purpose Physicians work increasingly in larger organizations across different health care delivery systems. This systematic review examines the published empirical literature on organizational commitment among physicians within an international context. Design A systematic, PRISMA-guided review examining studies of organizational commitment among physicians published over time. Four article databases and a combination of appropriate search terms aided in identifying relevant articles. Findings Key findings inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Dawon Baik et al’s research focused on nurses also supported our results and suggested a supportive team atmosphere, such as sufficient psychological safety, could mitigate workplace frustration and make employees more satisfied with their jobs and more likely to stay in their jobs. 19 Our findings also echo Hoff et al’s observation 11 that workplaces in which physicians felt in control of their jobs without undue stress and were satisfied with their jobs were likely to gain enhanced commitment. As negative psychological processes often have stronger effects than positive ones, 55 (reducing) job burnout offers a substantial way to counteract commitment issues induced by the lack of psychological safety.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Dawon Baik et al’s research focused on nurses also supported our results and suggested a supportive team atmosphere, such as sufficient psychological safety, could mitigate workplace frustration and make employees more satisfied with their jobs and more likely to stay in their jobs. 19 Our findings also echo Hoff et al’s observation 11 that workplaces in which physicians felt in control of their jobs without undue stress and were satisfied with their jobs were likely to gain enhanced commitment. As negative psychological processes often have stronger effects than positive ones, 55 (reducing) job burnout offers a substantial way to counteract commitment issues induced by the lack of psychological safety.…”
Section: Discussionsupporting
confidence: 86%
“…9 , 10 The disparity between professional commitment and organizational commitment creates a paradox where those who benefit more from training may have a higher possibility of turnover because of high job marketability and low affective commitment. 8 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians tend to have lower levels of organizational commitment than other health care workers, regardless of country, personal characteristics, type of work, or place of employment [ 87 ]. However, they tend to be more satisfied with their work than nurses in the same hospitals [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, they tend to be more satisfied with their work than nurses in the same hospitals [ 88 ]. In their case, the variables related to organizational commitment are: age and job satisfaction [ 87 ]. On the other hand, nurses tend to be more satisfied with their work climate and more committed to their organization [ 43 ].…”
Section: Resultsmentioning
confidence: 99%